Diurnal Harvest Cycle and Sap Composition Affect Under-Skin Browning in ‘Honey Gold’ Mango Fruit - San, Anh T.; Hofman, Peter J.; Joyce, Daryl C.; Macnish, Andrew J.; Marques, Jose R.; Webb, Richard I.; Li, Guoqin; Smyth, Heather E. (Frontiers in Plant Science, 2019)
Under-Skin Browning (USB) is an unsightly physiological disorder that afflicts ‘Honey Gold’ mango fruit. USB symptoms develop after harvest upon the interaction of physical abrasion and physiological chilling stresses. Less understood pre-harvest and / or harvest factors may also influence fruit susceptibility to USB. In this study, we examined the impact of harvest time during the diurnal cycle and fruit sap components on USB development. Fruit were harvested at 4–6-hour intervals, lightly abraded with sandpaper to simulate vibration damage during refrigerated road transport, held at 12 ± 1ºC for 6 d, transported to the research facilities and ripened before USB assessment. Spurt and ooze sap from the fruit were collected at each harvest time. The samples were separated and analysed by gas-chromatography mass spectrometry. Fruit harvested at 1000, 1400, and 1800 h had 3–5-fold higher incidence of USB than did those picked at 2200, 0200, and 0600 h. Sap concentrations of the key aroma volatile compounds 2-carene, 3-carene, α-terpinene, p-cymene, limonene, and α-terpinolene were higher for fruit harvested at 1400 h compared to those picked at other times. In the fruit harvested in the afternoon, abraded skin treated with spurt sap sampled at 1400 h had 14.3-fold and 29.0-fold higher incidence and severity, respectively, of induced browning than did those treated with sap collected at 0600 h. The results showed that fruit harvested in the afternoon were more susceptible to USB than those picked at night or in early morning. The diurnal variation in fruit sensitivity was evidently associated with specific compositional differences in sap phytotoxicity. Topical application to the fruit skin of pure terpinolene and limonene resulted in induced USB damage, whereas pure carene and distilled water did not. Microscopy examination showed that while skin damage caused by pure terpinolene and limonene were not identical to USB per se, similarities suggested that sap components cause USB under inductive commercial conditions. Considered collectively, these findings suggest that night and early morning harvesting will reduce USB and thus improve the postharvest quality of ‘Honey Gold’ mango fruit.